Specific surface of oxisols and its relationship with water retention - Ruiz, Hugo Alberto; Sarli, Guillermo Oliverio; Gonçalves Reynaud Schaefer, Carlos Ernesto; Filgueira, Roberto Raul; Silva de Souza, Fabiana (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The specific surface area of soil samples was estimated by the method of nitrogen adsorption at 78 K, and it was related to the water retention capacity, clay content, cation exchange capacity, and the amount of water retained on the exposed soil surface, in an approximation of superimposed layers. Twenty seven Oxisols were investigated. Soil moisture retention was studied at water potentials -33, -500, -1000 and -1500 kPa. The specific surface area was positively correlated to soil moisture and with clay content. No relationship was found between specific surface area and cation exchange capacity. Between specific surface area and soil organic content only a weak correlation was found. The specific surface area was related with soil moisture content by linear equations obtained by the regression method of data, for each water potential applied. The results showed that the specific surface area of these Oxisols can be reasonable estimated by water retention in a wide range of matrix potentials. Finally, from the obtained data on specific surface area and water retention it was possible to estimate the thickness of the water film covering the entire surface of the soil pores exposed to the air.